2012
DOI: 10.1108/17505931211265435
|View full text |Cite
|
Sign up to set email alerts
|

Perceived ethics of online retailers and consumer behavioral intentions

Abstract: Purpose -The purpose of this study is to examine the effects of consumers' perception of online retailers' ethical behavior on consumer purchase and revisit intentions. Design/methodology/approach -A sample of 259 online shoppers was employed to test the relationships between perceived ethics of online retailers and the intention to revisit and purchase. The measurement model and structural relationships were estimated using AMOS 18. Findings -Results show that perceived ethics of an Internet retailer's websit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
137
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(160 citation statements)
references
References 97 publications
(110 reference statements)
19
137
2
2
Order By: Relevance
“…In that context, the findings reveal that trust, perceived ease of use, perceived usefulness and enjoyment are significant positive predictors of customers' repurchase intentions (Chiu et al, 2009). As regards the effects of consumers' perception of online retailers' ethical behaviour on consumer purchase and revisit intentions it was found that perceived ethics of an Internet retailer's website significantly affected consumers' trust and attitudes to the retailer's website that eventually had positive impacts on purchase and revisit intentions (Limbu et al, 2012). Furthermore, to enhance customer purchase intentions, online stores should develop marketing strategies to better address the trustworthiness, reliability, and responsiveness of web-based services (Lee & Lin, 2005).…”
Section: Literature Reviewmentioning
confidence: 88%
“…In that context, the findings reveal that trust, perceived ease of use, perceived usefulness and enjoyment are significant positive predictors of customers' repurchase intentions (Chiu et al, 2009). As regards the effects of consumers' perception of online retailers' ethical behaviour on consumer purchase and revisit intentions it was found that perceived ethics of an Internet retailer's website significantly affected consumers' trust and attitudes to the retailer's website that eventually had positive impacts on purchase and revisit intentions (Limbu et al, 2012). Furthermore, to enhance customer purchase intentions, online stores should develop marketing strategies to better address the trustworthiness, reliability, and responsiveness of web-based services (Lee & Lin, 2005).…”
Section: Literature Reviewmentioning
confidence: 88%
“…Moreover, inconsistent result also observes the mediating effect of attitude on the relationship of the other linkages [14], [17], [27], [28], [30]- [34]. Thus, this hypothesis ought to be investigated further due to inconsistent results as well as to increase direct selling sectors especially in Thailand.…”
Section: Literature Reviewmentioning
confidence: 96%
“…This managerial gap has indicated that direct selling companies are worried about pyramid schemes and internet fraud which can be the main cause of bad direct selling corporate image that might threaten their legitimate business [13]. The increasing number of pyramid schemes and internet frauds (internet marketing) cases have created problems leading to the negative attitude [10], distrust [14], negative perceived value [15] and consequently leading to the bad corporate image of direct selling companies [12]. Distrust in consumer attitude as a result of internet fraud in Thailand [16] has affected consumers' attitudes towards the products or services they purchase [2], [3].…”
Section: Research Problemmentioning
confidence: 99%
See 2 more Smart Citations